A 316L stainless steel repairing method based on FeCrNi medium-entropy alloy additive filling and microstructure-residual stress synergistic regulation

CN122955962APending Publication Date: 2026-10-23NANJING UNIV OF AERONAUTICS & ASTRONAUTICS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611200042.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-06
Publication Date
2026-10-23

AI Technical Summary

Benefits of technology

[0028](1)本发明采用的近等原子比FeCrNi中熵合金与316L不锈钢具有相同的主要金属元素体系,有利于降低异质修复界面的冶金不相容风险。近等原子比多主元固溶体可为修复区提供固溶强化作用,同时其Cr含量高于316L不锈钢,可为稳定钝化膜的形成提供成分基础,从而促进修复区强度与耐腐蚀性能的协同改善。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HSA0000307686200000011
    Figure HSA0000307686200000011
  • Figure HSA0000307686200000021
    Figure HSA0000307686200000021
  • Figure HSA0000307686200000022
    Figure HSA0000307686200000022
Patent Text Reader

Abstract

The application discloses a 316L stainless steel repairing method based on FeCrNi medium-entropy alloy additive filling and structure-residual stress synergistic regulation and control. The method comprises the following steps: performing mechanical cleaning and geometric normalization on a damage or defect area of a 316L stainless steel base to form a controllable boundary repair groove; then, using a near-equiatomic FeCrNi medium-entropy alloy powder as a filling material, performing layer-by-layer filling on the repair groove by adopting laser directional energy deposition, and milling and flattening the overfilling layer; then, performing multi-pass friction stir processing along the length direction of the repair area until complete coverage is achieved, so that defect repairing and structure homogenization are realized; finally, performing laser shock peening on the surface of the processing area to introduce residual compressive stress into the surface layer. The method removes the damage of the 316 base, and couples the additive filling, structure regulation and control and residual stress regulation and control of the repair area into a continuous process, so that the compactness, interface bonding stability, strength-plasticity matching, corrosion resistance and low-temperature service reliability of the repair area can be synergistically improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of metal component repair and surface strengthening technology. Specifically, it relates to a method for laser-directed energy deposition filling of damaged areas of 316L stainless steel using FeCrNi medium-entropy alloy powder, and for achieving full-thickness microstructure control and surface residual stress control of the repair area through sequential friction stir processing and laser shock peening. Background Technology

[0002] 316L austenitic stainless steel is widely used in chemical equipment, marine engineering, cryogenic containers, and complex load-bearing components. Its service environment typically involves corrosive media, temperature variations, and mechanical loads. Damage such as wear, corrosion pits, cracks, or localized thinning formed during service often exhibits irregular morphologies. Direct additive filling can easily lead to decreased molten pool stability due to abrupt defect boundaries and surface contamination, resulting in problems such as incomplete fusion, porosity, and inconsistent interface quality. Therefore, mechanical cleaning and geometric normalization of the defect area before repair is beneficial for obtaining stable and repeatable repair boundaries.

[0003] Using 316L homogeneous powder for repair is beneficial for maintaining compositional continuity and metallurgical compatibility, but its main function is still biased towards homogeneous filling and geometric restoration. The strength and corrosion resistance of the repaired area are mainly limited by the 316L material itself and the deposited structure, and the room for control in the design of repair material composition is relatively limited.

[0004] To further improve the overall performance of the repair zone, it is necessary to introduce a filler material that enhances both strength and corrosion resistance, while maintaining compatibility with the main elements of the 316L matrix. The FeCrNi medium-entropy alloy, with Fe, Cr, and Ni as its main components, shares the same main metallic element system as 316L stainless steel, thus exhibiting good compositional compatibility and metallurgical bonding. This FeCrNi medium-entropy alloy employs a near-equiatomic ratio composition design, with Fe, Cr, and Ni atomic percentages ranging from 32.0% to 34.0%, and a nominal composition of Fe33.3Cr33.3Ni33.3. Near-equiatomic ratio multi-principal element solid solutions can increase dislocation motion resistance through lattice distortion and multi-element interactions, providing solid solution strengthening for the repair zone. Simultaneously, compared to 316L stainless steel, the FeCrNi medium-entropy alloy has a higher Cr content, providing a compositional basis for the formation of a stable and dense Cr-rich passivation film on the surface of the repair zone. Therefore, this near-equiatomic ratio FeCrNi medium-entropy alloy provides a material basis for the synergistic improvement of the strength and corrosion resistance of the repair zone.

[0005] Therefore, when near-equal atomic ratio FeCrNi medium-entropy alloys are used for the repair of 316L stainless steel, they are not simply a replacement for 316L homogeneous powder to achieve a similar composition. Rather, they are designed as filler materials to meet the requirements of strength, corrosion resistance, and low-temperature service reliability in the repair area. While maintaining compatibility with the main elemental system of 316L stainless steel, this material can leverage the multi-principal element solid solution strengthening effect and the corrosion resistance provided by the high Cr content, thereby improving the overall performance of the repair area.

[0006] However, the laser-directed energy deposition process involves rapid melting and solidification, and the deposited repair area may have problems such as coarse columnar crystals, local component segregation, pores, lack of fusion and residual tensile stress, making it difficult to meet the high reliability service requirements by relying solely on the filler material itself.

[0007] Friction stir processing can homogenize the microstructure, compact and close defects, and refine grains in the additive repair zone through intense plastic deformation and dynamic recrystallization of the solid phase. Laser shock annealing can introduce residual compressive stress on the surface of the repair zone and improve the zone's resistance to surface crack initiation and propagation.

[0008] In existing technologies, laser-directed energy deposition, friction stir processing, and laser shock peening are usually used as relatively independent repair or post-processing methods. There is a lack of integrated design methods for 316L stainless steel repair that integrate the design of filling materials, the control of the microstructure of the full thickness of the repair area, and the control of residual stress on the surface. Summary of the Invention

[0009] 1. This invention aims to solve the problems existing in the repair of local damage of 316L stainless steel, such as the difficulty in stable filling of irregular damage boundaries, the limited space for improving the performance of homogeneous filler materials, the uneven structure and defects in the additive repair area, and the insufficient residual tensile stress and damage resistance of the surface layer. It provides a repair method that combines FeCrNi medium-entropy alloy additive filling, full-thickness microstructure control by friction stir processing, and control of residual stress on the surface layer by laser shock.

[0010] To achieve the above objectives, the invention adopts the following technical solution:

[0011] A repair method for 316L stainless steel based on FeCrNi medium-entropy alloy additive filling and synergistic regulation of microstructure and residual stress includes the following steps:

[0012] S1, machining defective areas with wear, corrosion pits, cracks or local thinning on a 316L stainless steel substrate to remove defective material and form a repair groove extending along the length of the substrate, wherein the repair groove has a controllable bottom, sidewalls and groove opening boundary.

[0013] S2, after cleaning and surface activation treatment of the repair groove, FeCrNi medium-entropy alloy powder is used as the filling material, and laser directional energy deposition is used to fill the repair groove layer by layer under inert gas protection until the deposition layer is higher than the surface of the 316L stainless steel substrate, forming an overfilled repair layer.

[0014] S3, the overfilled repair layer is milled and leveled so that the surface of the repair layer forms a continuous plane with the surface of the 316L stainless steel substrate;

[0015] S4, perform multi-pass friction stir processing on the repair area after milling and leveling, so that the multi-pass friction stir processing area covers the repair area in the width direction and covers the full thickness of the additive repair layer in the depth direction and extends to the metallurgical bonding interface between the repair layer and the substrate, thereby obtaining a homogenized repair area.

[0016] S5, an absorption layer and a constraint layer are provided on the surface of the tissue homogenization repair zone, and laser shock peening is performed on the surface area corresponding to the multi-pass stirring friction processing zone to form a residual compressive stress strengthening layer on the surface of the repair zone.

[0017] The core of this invention lies in matching the action area and depth of laser-directed energy deposition, friction stir processing, and laser shock peening. Specifically, laser-directed energy deposition is used to restore the geometry of the damaged area and provide a material basis for synergistic improvement in the strength and corrosion resistance of the repaired area; friction stir processing is used to control the full thickness of the additive repair layer and the microstructure and defects of its metallurgical interface with the matrix; and laser shock peening is used to control the residual stress state of the surface layer of the repaired area.

[0018] 2. Further, in step S1, the repair tank is mechanically ground and cleaned to remove oxide film, rust and impurities from the bottom and sidewalls of the repair tank, so as to improve the metallurgical bond between the FeCrNi medium entropy alloy additive repair layer and the 316L stainless steel substrate, and reduce the risk of additive defects such as incomplete fusion, porosity and inclusions.

[0019] Further, the particle size of the FeCrNi medium-entropy alloy powder in step S2 is 20-120 μm; by atomic percentage, the FeCrNi medium-entropy alloy powder comprises: Fe 32.0%-34.0%, Cr 32.0%-34.0%, and Ni 32.0%-34.0%, and the sum of the atomic percentages of Fe, Cr, and Ni is 100%; the nominal composition of the FeCrNi medium-entropy alloy powder is equiatomic Fe33.3Cr33.3Ni33.3.

[0020] Furthermore, the process parameters used in the laser directional energy deposition in step S2 include: laser spot diameter of 5-6 mm, defocusing amount of 25-35 mm, laser power of 1800-2200 W, scanning speed of 350-450 mm / min, powder feeding rate of 12-18 g / min, and powder carrier gas flow rate of 4-8 L / min.

[0021] Furthermore, in the laser directional energy deposition process of step S2, each layer adopts a serpentine reciprocating scanning path, the scanning directions of adjacent deposition layers are rotated 90° relative to each other, the inter-track overlap rate is 40% to 50%, and the inter-layer lift is 0.6 to 1.0 mm.

[0022] Furthermore, the inert gas mentioned in step S2 is argon, and the protective gas flow rate is 8-12 L / min.

[0023] Furthermore, the friction stir machining tool used in step S4 includes a shoulder and a tapered stirring pin; the shoulder diameter is 12mm, the root diameter of the stirring pin is 6mm, the end diameter of the stirring pin is 4mm, and the length of the stirring pin is 3mm; the length of the stirring pin is not less than the thickness of the additive repair layer after milling and leveling, and the end of the stirring pin extends beyond the metallurgical interface between the additive repair layer and the 316L stainless steel substrate by 0.1 to 0.5mm.

[0024] Furthermore, the friction stir processing described in step S4 is a multi-pass friction stir processing, with a stirring head rotation speed of 600 r / min, a travel speed of 40 mm / min, a center-to-center distance between passes of 2 mm, a downward pressure of 0.2 mm, and a single-pass processing length of 80 mm. The multi-pass friction stir processing adopts a serpentine reciprocating path, with adjacent passes arranged sequentially along the width direction of the repair area and partially overlapping.

[0025] Further, in step S5, an absorption layer and a constraint layer are sequentially set on the surface of the repair area after friction stir processing, and laser shock strengthening is performed using a nanosecond pulsed laser; the laser single pulse energy is 18-22J, the laser pulse width is 12-16ns, the spot diameter is 3-5mm, and the shock overlap rate is 50%-60%.

[0026] Furthermore, in step S5, the laser shock strengthening path scans along the length direction of the repair area and covers the strip area corresponding to the multi-pass friction stir processing area in the width direction, thereby forming a residual compressive stress strengthening layer on the surface of the repair area.

[0027] Compared with the prior art, the present invention has at least the following beneficial effects:

[0028] (1) The near-equal atomic ratio FeCrNi medium-entropy alloy used in this invention has the same main metallic element system as 316L stainless steel, which helps to reduce the risk of metallurgical incompatibility at the heterogeneous repair interface. The near-equal atomic ratio multi-principal element solid solution can provide solid solution strengthening for the repair zone, and its Cr content is higher than that of 316L stainless steel, which can provide a compositional basis for the formation of a stable passivation film, thereby promoting the synergistic improvement of the strength and corrosion resistance of the repair zone.

[0029] (2) This invention uses laser-directed energy deposition technology to locally repair 316L stainless steel. Compared with the traditional integral fusion welding repair process, its heat input area and heat-affected zone are relatively concentrated, which helps to reduce the risk of overall deformation and microstructure deterioration of the substrate. By standardizing the tank shape, using inert gas protection, adjusting the overlap rate and interlayer scanning direction, the stability of the deposition path and molten pool can be improved, reducing the risk of defects such as incomplete fusion, porosity, and interface fluctuations.

[0030] (3) The present invention enables the stirring friction processing zone to cover the full thickness of the additive repair layer and act on the metallurgical interface between the repair layer and the substrate. It can achieve pore compaction, local defect closure, coarse columnar crystal breakage and equiaxed fine grain formation through solid phase plastic flow and dynamic recrystallization, thereby improving the uniformity of the structure and interface stability of the additive repair zone.

[0031] (4) Laser shock strengthening can be implemented on the basis of full thickness microstructure control in friction stir processing. Residual compressive stress can be introduced into the surface layer of the repair area, so that the repair area forms a gradient strengthening state combining full thickness microstructure control and surface residual stress control, thereby improving the repair area's ability to resist the initiation and propagation of surface cracks.

[0032] (5) By constraining the spatial coverage relationship of laser directional energy deposition, friction stir processing and laser shock strengthening, the present invention enables the three processes to respectively undertake the functions of heterogeneous material filling and geometric restoration, full thickness tissue homogenization and surface damage resistance strengthening, thereby achieving synergistic matching between repair material design and multi-process treatment. Attached Figure Description

[0033] Figure 1 This is a flowchart of the process flow of the present invention.

[0034] Figure 2 This is a schematic diagram of (a) the composite repair process and (b) the path planning of the present invention.

[0035] Figure 3 These are engineering stress-strain curves at room temperature and 77K for a 316L stainless steel substrate, a sample repaired only by laser-directed energy deposition, a sample treated by laser-directed energy deposition and friction stir processing, and a sample treated by laser-directed energy deposition, friction stir processing, and laser shock peening.

[0036] Figure reference numerals: 1-Laser beam; 2-Protective gas; 3-Powder feed flow; 4-316L stainless steel substrate; 5-FeCrNi medium-entropy alloy additive repair layer; 6-Repair groove; 7-Clamping end; 8-Stirring needle; 9-Shoulder; 10-Friction stirring processing zone; 11-Pulsed laser beam; 12-Laser shock reinforcement zone. Detailed Implementation

[0037] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of protection of the present invention.

[0038] In this embodiment, FeCrNi medium-entropy alloy powder is used to repair a 316L austenitic stainless steel matrix, and the additive repair area is further processed through friction stir processing and laser shock annealing. Through the above treatments, defects are compacted and closed, coarse columnar crystals are broken up and grains are refined within the additive repair area, and residual compressive stress is introduced into the surface layer of the repair area, thereby improving the mechanical properties and corrosion resistance of the repair area.

[0039] Example 1

[0040] S1, Matrix pretreatment:

[0041] A 316L stainless steel plate with dimensions of 100mm×100mm×25mm was selected as the substrate to be repaired. A trapezoidal repair groove was milled along the length of the original damaged or pre-fabricated defect area. The bottom width of the trapezoidal repair groove was 20mm, the depth was 2.5mm, and the angle between the inclined sidewall and the bottom of the groove was 30°.

[0042] The bottom and sidewalls of the repair groove were sanded stepwise with sandpaper to remove oxide film, rust, and impurities. The sample was then ultrasonically cleaned in anhydrous ethanol for 15 minutes, removed, and dried for later use. This machining and surface cleaning process was used to obtain a repair groove with stable boundaries and a clean metallurgical bonding surface.

[0043] S2, Laser-Directed Energy Deposition Remediation:

[0044] Overfill repair using laser-directed energy deposition (EDD) was performed on FeCrNi medium-entropy alloy powder, which was atomized from gas. The powder had a particle size of 20–120 μm and, by atomic percentage, comprised 32.0%–34.0% Fe, 32.0%–34.0% Cr, and 32.0%–34.0% Ni, with the sum of the atomic percentages of the three elements being 100%. The nominal composition of the powder was equiatomic Fe33.3Cr33.3Ni33.3.

[0045] Select The process parameters for the laser-guided energy deposition equipment are set as follows: laser spot diameter is 5-6 mm, defocusing amount is 30 mm, laser power is 2200 W, scanning speed is 400 mm / min, powder feeding rate is 15 g / min, powder carrier gas flow rate is 6 L / min, and protective gas flow rate is 10 L / min.

[0046] A serpentine reciprocating scanning method was used in the repair tank of a 316L stainless steel substrate. The scanning direction of adjacent deposited layers was rotated by 90°, the overlap rate between passes was 40%, and the interlayer lift was 0.8 mm. Deposition was carried out layer by layer from the bottom of the repair tank until the deposited layer was 0.5 mm above the substrate surface, forming an overfilled repair layer.

[0047] Argon gas was used for simultaneous protection during the deposition process to reduce the oxidation level of the molten pool and the deposited layer. After deposition, the macroscopic morphology of the additive repair layer was inspected, and surface and internal defects were checked using penetrant testing or X-ray inspection.

[0048] S3, Milling and Leveling:

[0049] The overfilled repair layer is milled to remove the excess deposit above the 316L stainless steel substrate surface, so that the repair layer surface and the substrate surface form a continuous plane.

[0050] After milling, the actual thickness of the additive repair layer is measured, and the length and insertion depth of the stirring pin are determined according to the thickness of the repair layer to ensure that the tip of the stirring pin can act on the metallurgical interface between the repair layer and the substrate.

[0051] S4, Friction Stir Processing:

[0052] Multiple passes of friction stirring are performed along the length of the repair area. The stirring tool used includes a clamping end, a shoulder, and a stirring pin connected in sequence. The clamping end is connected to an external drive device, which drives the stirring tool to rotate around its own axis and move along the length of the repair area.

[0053] The shoulder diameter is 12mm; the stirring needle is a conical structure made of tungsten-rhenium alloy, with a root diameter of 6mm, an end diameter of 4mm, and a length of 3mm.

[0054] The parameters for friction stir machining are set as follows: stirring head speed is 600 r / min, travel speed is 40 mm / min, downward pressure is 0.2 mm, center distance between passes is 2 mm, and single pass machining length is 80 mm.

[0055] A serpentine multi-pass friction stirring process is performed along the length of the repair area, for a total of 15 passes, with a theoretical coverage width of:

[0056] 12mm + (15-1) × 2mm = 40mm.

[0057] The adjacent passes partially overlap, ensuring that the friction stir processing zone continuously covers the additive repair zone in the width direction. The tip of the stirring pin extends approximately 0.5 mm beyond the metallurgical interface between the additive repair layer and the substrate to promote plastic flow and homogenization of the material near the interface.

[0058] During the processing, the angle between the axis of the stirring tool and the surface of the workpiece is 0° to 3°.

[0059] S5, Laser Shock Enhancement:

[0060] The surface of the repair area after friction stir machining is milled, ground, or polished to achieve a surface roughness Ra ≤ 1.6 μm. Subsequently, an absorption layer is applied to the surface to be treated, and a constraint layer is applied on top of the absorption layer.

[0061] The absorbent layer is black tape, aluminum foil, or a black absorbent coating, and the constraint layer is a flowing water layer.

[0062] The surface of the repair area was laser-shock strengthened using a nanosecond pulsed laser. The laser single-pulse energy was 18–22 J, the laser pulse width was 12–16 ns, the spot diameter was 3–5 mm, and the spot overlap rate was 50%–60%.

[0063] The laser shock peening path scans along the length of the repair area and covers a strip region in the width direction corresponding to the multi-pass friction stir processing area. Laser shock peening induces plastic deformation on the surface of the repair area and introduces residual compressive stress.

[0064] Comparative Example 1

[0065] This comparative example provides a method for repairing 316L austenitic stainless steel using laser-directed energy deposition (EDD). The difference between this method and Example 1 is that only the FeCrNi medium-entropy alloy undergoes laser-directed energy deposition filling and milling leveling; subsequent friction stir processing and laser shock peening are not performed.

[0066] Comparative Example 2

[0067] This comparative example provides a method for repairing 316L austenitic stainless steel using laser-directed energy deposition (LDED) and friction stir processing. The difference between this method and Example 1 is that it involves LDED filling of FeCrNi medium-entropy alloy, milling and leveling, and friction stir processing, without laser shock peening.

[0068] Comparative Example 3

[0069] This comparative example uses 316L homogeneous powder as the filler material and sequentially undergoes laser-directed energy deposition filling, milling and leveling, friction stir processing, and laser shock peening. Except for the filler powder composition, all other process parameters are the same as in Example 1.

[0070] By comparing Example 1 with Comparative Example 3, the contributions of FeCrNi medium-entropy alloy filler material and the composite process of friction stir processing and laser shock peening to the performance of the repaired area can be distinguished.

[0071] (6) Organization and performance testing

[0072] The microstructure and properties of the 316L stainless steel matrix, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Example 1 were characterized.

[0073] The defects, interface morphology, and elemental distribution of the repair area were characterized using optical microscopy, scanning electron microscopy, and energy dispersive spectroscopy. Grain size, grain boundary characteristics, and local orientation differences were analyzed using EBSD. The phase composition of the repair area was analyzed using XRD or TEM. The residual stress distribution at different depths was analyzed using X-ray diffraction residual stress testing combined with layer-by-layer electrolytic polishing. The corrosion resistance of the repair area was evaluated using electrochemical polarization and electrochemical impedance spectroscopy. The mechanical properties of the repair area were evaluated using room temperature and 77K tensile tests.

[0074] For each condition, there should be no fewer than three tensile specimens, and the average value and standard deviation of yield strength, tensile strength and elongation after fracture should be reported respectively.

[0075] Depend on Figure 3 The room temperature engineering stress-strain curves show that Comparative Example 1, which was repaired only by laser-directed energy deposition, has lower yield strength and tensile strength, and its plasticity is lower than that of the 316L stainless steel matrix. This is because the laser-directed energy deposition repair area contains defects such as coarse columnar crystals, local porosity, lack of fusion, and uneven microstructure, which easily lead to stress concentration and premature fracture.

[0076] Compared with Comparative Example 1, Comparative Example 2 showed improved yield strength, tensile strength, and elongation after fracture after friction stir processing. This indicates that the intense plastic deformation and dynamic recrystallization induced by friction stir processing can break up coarse columnar crystals, refine grains, and compact and close local defects, thereby improving the strength-plasticity matching of the additive repair zone.

[0077] After laser shock strengthening, the yield strength of Example 1 was further improved compared with Comparative Example 2, indicating that the surface plastic deformation, high-density dislocations and residual compressive stress introduced by laser shock strengthening can further improve the ability of the repaired area to resist plastic deformation and crack initiation.

[0078] Depend on Figure 3The stress-strain curves at 77K show that the yield strength and tensile strength of all samples increased as the test temperature decreased from room temperature to 77K. Example 1 maintained high strength and certain plasticity at 77K, indicating that the FeCrNi medium-entropy alloy filling, full-thickness microstructure control through friction stir processing, and residual stress control on the surface layer via laser shock stabilization are beneficial for improving the low-temperature service performance of the repaired area.

[0079] Further electrochemical testing results showed that, compared with the 316L homogeneous powder-repaired sample, the sample repaired with FeCrNi medium-entropy alloy powder exhibited a higher pitting potential and a lower corrosion current density. This indicates that a higher Cr content can improve the stability of the passivation film on the repaired area, thereby enhancing its corrosion resistance. Specific test data should be supplemented based on actual experimental results.

[0080] This invention provides a method for repairing 316L stainless steel based on FeCrNi medium-entropy alloy additive filling and synergistic regulation of microstructure and residual stress. This method achieves a composite repair structure in the repair area through geometric normalization of the damaged region, FeCrNi medium-entropy alloy laser additive filling, full-thickness microstructure regulation via friction stir processing, and surface residual stress regulation via laser shock irradiation. This results in a structure where the additive filling zone, the microstructure homogenization zone, and the surface residual compressive stress strengthening layer are nested within each other. This improves the density, interface stability, strength-ductility matching, corrosion resistance, and low-temperature service reliability of the repair area.

[0081] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for repairing 316L stainless steel based on FeCrNi medium-entropy alloy additive filling and synergistic regulation of microstructure and residual stress, characterized in that, Includes the following steps: S1, machining defective areas with wear, corrosion pits, cracks or local thinning on a 316L stainless steel substrate to remove defective material and form a repair groove extending along the length of the substrate, wherein the repair groove has a controllable bottom, sidewalls and groove opening boundary. S2, after cleaning and surface activation treatment of the repair tank, FeCrNi medium-entropy alloy powder is used as the filling material, and laser directional energy deposition is used to deposit and fill the repair tank layer by layer under inert gas protection until the deposited layer is higher than the surface of the 316L stainless steel substrate, forming an overfilled repair layer. S3, the overfilled repair layer is milled and leveled so that the surface of the repair layer forms a continuous plane with the surface of the 316L stainless steel substrate; S4, perform multi-pass friction stirring processing on the milled and leveled repair area so that the multi-pass friction stirring processing area covers the repair area in the width direction and covers the full thickness of the laser directional energy deposition repair layer in the depth direction and extends to the metallurgical interface between the repair layer and the substrate, thereby obtaining a homogenized repair area. S5, an absorption layer and a constraint layer are set on the surface of the tissue homogenization repair area. The surface projection area of ​​the multi-pass stirring friction processing area is used as the laser shock strengthening area. Laser shock strengthening is performed on the surface layer of the repair area so that the laser shock strengthening area at least covers the repair area, thereby obtaining a 316L stainless steel repair part with FeCrNi medium entropy alloy additive filling, full thickness tissue homogenization and surface residual compressive stress control.

2. The method according to claim 1, characterized in that, The repair groove is a trapezoidal repair groove, a rectangular repair groove, a U-shaped repair groove formed by mechanical milling, or a combined section repair groove formed according to the normalization of the original defect boundary.

3. The method according to claim 2, characterized in that, The repair groove is a trapezoidal repair groove with a bottom width of 15-25mm, a depth of 1.5-4.0mm, and an angle of 25°-45° between the inclined sidewall and the bottom of the groove.

4. The method according to claim 3, characterized in that, The 316L stainless steel substrate has dimensions of 100mm×100mm×25mm. The trapezoidal repair groove extends through or nearly through the substrate along its length. The groove bottom is 20mm wide and 2.5mm deep, and the angle between the inclined sidewall and the groove bottom is 30°.

5. The method according to claim 1, characterized in that, The FeCrNi medium-entropy alloy powder comprises, by atomic percentage: Fe 32.0%–34.0%, Cr 32.0%–34.0%, and Ni 32.0%–34.0%, and the sum of the atomic percentages of Fe, Cr, and Ni is 100%; the nominal composition of the FeCrNi medium-entropy alloy powder is equiatomic Fe33.3Cr33.3Ni33.3, and the powder particle size is 20–120 μm.

6. The method according to claim 1, characterized in that, The process parameters used in the laser-directed energy deposition include: laser spot diameter of 5-6 mm, defocusing amount of 25-35 mm, laser power of 1800-2200 W, scanning speed of 350-450 mm / min, powder feed rate of 12-18 g / min, powder carrier gas flow rate of 4-8 L / min, protective gas flow rate of 8-12 L / min, and the protective gas is argon.

7. The method according to claim 1, characterized in that, In step S2, a serpentine reciprocating scanning path is used, the scanning direction of adjacent sedimentary layers is rotated 90° relative to the previous sedimentary layer, the inter-track overlap rate is 40% to 50%, and the inter-layer uplift is 0.6 to 1.0 mm.

8. The method according to claim 1, characterized in that, The friction stir machining tool used in step S4 includes a shoulder and a tapered stirring pin. The diameter of the shoulder is 10-14 mm, the length of the stirring pin is 2.5-3.5 mm, the diameter of the root of the stirring pin is 5-7 mm, and the diameter of the tip of the stirring pin is 3-5 mm. The length of the stirring pin is not less than the thickness of the additive repair layer after milling and leveling, and the tip of the stirring pin extends 0.1-0.5 mm beyond the metallurgical interface between the additive repair layer and the substrate.

9. The method according to claim 1, characterized in that, In step S4, the rotational speed of the friction stir processing is 500-800 r / min, the travel speed is 30-60 mm / min, the pressure is 0.1-0.3 mm, and the center-to-center distance between passes is 1-3 mm. In the multi-pass friction stir processing, each single-pass processing path extends along the length of the repair area, and adjacent passes are arranged sequentially along the width direction and partially overlap, so that the friction stir processing area forms a continuous strip area with basically parallel side boundaries.

10. The method according to claim 9, characterized in that, The multi-pass friction stir machining uses a shoulder with a diameter of 12mm, a center-to-center spacing of 2mm between passes, and a single pass length of 80mm. A total of 15 passes are performed, so that the theoretical coverage width of the friction stir machining is 40mm, and the coverage width is not less than the width of the laser-directed energy deposition repair area.

11. The method according to claim 1, characterized in that, The absorption layer in step S5 is black tape, aluminum foil, or a black absorbing coating, and the constraint layer is a flowing water layer or a transparent solid constraint layer. The laser shock peening uses a nanosecond pulsed laser with a single pulse energy of 18–22 J, a pulse width of 12–16 ns, a spot diameter of 3–5 mm, and an impact overlap rate of 50%–60%. The laser shock peening path scans along the length of the repair area and covers a strip area corresponding to the multi-pass stirring friction processing area in the width direction.

12. The method according to claim 1, characterized in that, Before laser shock peening, the surface of the multi-pass friction stir processing zone is milled, ground, or polished to make the surface roughness Ra≤1.6μm; after laser shock peening, a residual compressive stress strengthening layer and a surface plastic deformation strengthening layer are formed on the surface of the repair zone.

13. A 316L stainless steel repair part prepared by the method according to any one of claims 1 to 12, characterized in that, The system includes a 316L stainless steel substrate, a FeCrNi medium-entropy alloy additive repair zone filled in the repair groove and metallurgically bonded to the substrate, a multi-pass friction stir processing zone covering the full thickness of the additive repair zone and extending to the metallurgical bonding interface, and a laser shock residual compressive stress strengthening layer located on the surface of the multi-pass friction stir processing zone; the FeCrNi medium-entropy alloy additive repair zone, the multi-pass friction stir processing zone, and the laser shock residual compressive stress strengthening layer are spatially nested from the inside to the outside.